Spectrum of Unnatural Deaths in Palpa, Nepal: Autopsy Based Study - Atreya, Alok; Nepal, Samata; Gyawali, Pushpa Raj (Birat Journal of Health Sciences, 2019)
Introduction: Analysis of unnatural death of a community reflects the cause of death and socio-economic strata of that society. Medico-legal autopsies are conducted under the ordinance of legal authority in all cases of unnatural deaths. Objectives: The present study is aimed to determine the spectrum of unnatural deaths in Tansen Municipality of Papla district of Province 5, Nepal. Methodology: This autopsy based study was conducted during the Nepalese fiscal calendar 2074/75 which includes all the cases autopsied in the mortuary of District Hospital Tansen, Palpa. Results: Of total 184 medico-legal autopsies road traffic accidents (RTA) was the leading cause of death (n=53, 28.8%) followed by hanging (n=43, 23.41%) and burn (n=33, 17.9%). Of the 33 cases of burn 25 were females (13.6%) and 8 males (4.3%). There were 13 cases (7.1%) of obscure autopsy. Conclusion: The present study reflected the spectrum of unnatural deaths in Palpa district of province 5, Nepal which revealed RTA as a leading cause of death, followed by hanging. When gender was taken into account it was revealed that more females succumbed to death due to complications of the burn injuries sustained. Unnatural death due to fatal poisoning was least common finding of the present study although poisoning is one of the leading causes of deliberate self-harm globally. Proposal/program of collaboration of District Hospital with other tertiary care centres of Palpa district is the need of the hour which would provide specific, timely and expert approach to range of medicolegal cases.